Pengaruh Sistem Pengendalian Intern Terhadap Kualitas Laporan Keuangan Pemerintah Daerah - BRM Suryo Triono; Septiana Novita Dewi (Jurnal Akuntansi dan Pajak, 2020)
The purpose of this study is to provide empirical evidence about the analysis of the influence of the internal control system on the quality of local government financial reports (Empirical Study on SKPD of Sukoharjo Regency). The analysis technique used in this study is the data quality test which includes validity test and reliability test, classic assumption test which includes normality test, multicollinearity test and heteroscedasticity test, multiple linear regression equation test, and hypothesis test which includes t test, F test, and R2 Test. The results of the study indicate that the Control environment has a significant effect on the Quality of Local Government Financial Reports. Risk Assessment has a significant effect on the Quality of Local Government Financial Reports. Control activities have no significant effect on the Quality of Local Government Financial Reports. Information and Communication have a significant effect on the Quality of Local Government Financial Reports. Monitoring has a significant effect on the Quality of Local Government Financial Reports. The results of the F test show that there are significant independent variables together on the dependent variable. Based on R2 test results show that the ability of control environment variables, risk assessment, control activities, information and communication, and monitoring can explain the variable quality of local government financial statements of 69%. and the remaining 31% is explained by other independent variables